Character Recognition Through Wild Association: An Alternative in Learning Chinese Script for Beginners - LAM, Kai-Chee; ANG, Lay-Hoon; Kuan, Wee-Ling; Hoe, Foo-Terng (Issues in Language Studies, 2018)
Learning Chinese characters can be a daunting experience for the non-native learners. This quantitative study aims to experiment the effectiveness of ‘Wild Association’ on learners’ ability to learn Chinese characters, and to determine whether these learners who use ‘Wild Association’ demonstrate higher achievement in character recognition and character writing compared to learners who study Chinese characters by drilling. Consisting of 98 learners from the elementary level of Mandarin proficiency course in UNIMAS, the learners used their own imagination to learn Chinese characters, and at the same time, relating their own experience in doing so. Learners’ performance was measured through the pre-test and post-test in the form of dictation and character-recognition worksheet. The results indicate that ‘Wild Association’ is effective in helping learners to recognise and write characters, and is especially more effective in helping learners to recognise characters. However, learners who underwent traditional drilling approach still outperformed those who employed ‘Wild Association’. It can be concluded that ‘Wild Association’ is a possible alternative for teaching characters in the initial stage, when characters are still foreign to learners. The result implies that ‘Wild Association’ suits the learning style of learners nowadays.